Endovascular treatment of central venous obstruction as a complication of prolonged hemodialysis – Preliminary experience in a tertiary care center - Yadav, Mukesh K; Sharma, Madhurima; Lal, Anupam; Gupta, Vivek; Sharma, Ashish; Khandelwal, Niranjan (Indian Journal of Radiology and Imaging, 2015)
Background: Central venous disease is a serious complication in patients undergoing hemodialysis, often presenting with symptoms of venous hypertension. Treatment is aimed to provide symptomatic relief and to maintain hemodialysis access site patency. Aim: To describe our initial experience in the endovascular treatment of central venous stenosis or obstruction in patients undergoing hemodialysis. Settings and Design: This was a retrospective study carried out in a tertiary care center. Study duration was 24 months. Follow-up was variable. Materials and Methods: Eleven patients of chronic renal failure undergoing hemodialysis presented with central vein stenosis or obstruction having ipsilateral vascular access, between July 2012 and July 2014. All the patients underwent endovascular treatment and were analyzed retrospectively. Results and Conclusion: A total of 11 patients (4 male and 7 female) underwent 18 interventions for 13 stenotic segments during a time period of 2 years. Eight stenotic segments were in brachiocephalic vein, three in subclavian vein, and two in axillary veins. The technical success rate for endovascular treatment was 81.8%. Two patients underwent percutaneous transluminal angioplasty (PTA) alone and presented with restenosis later. Balloon angioplasty followed by stenting was done in seven patients, two of which required reintervention during follow-up. We found endovascular treatment safe and effective in treating central venous disease.
Keywords: Angioplasty; central venous stenosis; endovascular; hemodialysis; stenting